Morphometric study of atypical lumbar vertebrae and its physiological correlation - Amrish Tiwari,; Shilpa Pandey,; Deepak C Naik, (Universiti Kebangsaan Malaysia, 2015)
Background: The fixation of lumbar spine is needed for various spinal problems such as fracture in lumbar spine, resection of tumors in vertebral bodies, gross spondylolisthesis, and lumbar instabilities. Majority of pedicle morphometric studies are based on white population in different parts of the world, whereas only a few studies are available on Indian population. Objective: To report the results of a morphometric study of adult atypical lumbar vertebrae’s pedicles and correlate them physiologically to provide morphometric inputs for the use of this vertebral component in implants fixation in the population of Rewa, Madhya Pradesh, India. Materials and Methods: This study was conducted on 20 dry human atypical lumbar vertebrae obtained from Department of Anatomy, Shyam Shah Medical College, Rewa (Madhya Pradesh, India). Pedicle vertical height (h) and pedicle width (w) were measured with the help of a sliding vernier caliper. Results: Positive correlations have been found between height and width of dry human lumbar vertebrae. Conclusion: Results indicated that in Rewa region of central India, 15-mm Steffee pedicle screw can be used safely for atypical lumbar vertebrae.